Pengaruh Perubahan Budaya Organisasi Terhadap Kualitas Layanan di Sektor Kesehatan: Tinjauan Literatur Sistematis - Aloysius Arya Sanjaya; Imam Hanafi; Alfi Haris Wanto (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Organizational culture change in the healthcare sector has a significant impact on the quality of services provided. In a dynamic environment, healthcare organizations must be able to adapt their internal culture to face new challenges, such as technological developments, regulatory changes, and increasing expectations from patients and the public. This study aims to explore the effect of organizational culture change on the quality of healthcare services through a systematic literature review. The methodology used is the Systematic Literature Review (SLR) with data analysis from various relevant studies. The results show that cultural change that supports employee engagement and focuses on patient satisfaction can improve operational efficiency and service quality. However, challenges such as resistance to change and limited resources remain obstacles that must be overcome. The conclusion of this study emphasizes that organizational culture change is not only a strategic step to improve service quality, but also a long-term investment that can improve employee engagement and patient satisfaction.